Marketing of Library and information services at British Council Library Networks in India - Bhat, M. Ishwara (DESIDOC Journal of Library & Information Technology, 2003)
The paper outlines the marketing approaches used in the British Council Library Network in India. The market analysis is done in order to get a profile of the customers in these libraries. Excellent customer relations are maintained by delivering quality service. Customer interaction is a continuous process and this is ensured by conscious listening to the customers, meet the members programmes, questionnaires, surveys, and suggestion boxes. The libraries use promotional techniques such as mailshots, distribution of -publicity material, publicity through press and advertising in order to increase the customer base. Extension activities such as lectures and seminars attract the target customers to the library apart from furthering the social cause. http://dx.doi.org/10.14429/dbit.18.3.3398